Tindak Tutur Ilokusi Pada Tuturan Raditya Dika dan Henry Manampiring di Media Sosial Youtube - Istiqomah, Nur; Mardiningsih, Mardiningsih; Rosidah, Ilmiyatur (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research analyzes illocutionary speech acts in the speech of Raditya Dika and Henry Manampiring on YouTube social media, which aims to describe the form of illocutionary speech acts used by Raditya Dika and Henry Manampiring. The research method used is descriptive qualitative using the technique of watching and taking notes on YouTube videos. According to the theory used, namely Searle's theory. The research results show that Raditya Dika and Henry Manampiring use various forms of illocutionary speech acts, including assertive, directive, expressive, commissive and declarative. Assertive speech acts are the most dominant, reflecting the speaker's beliefs conveyed descriptively and informatively. This research provides in-depth insight into how to communicate and interact via social media platforms and can be a reference for further pragmatic research, especially regarding illocutionary speech acts.  Keywords: speech act; illocutionary; YouTube; pragmatics.